KAJIAN PRODUKTIVITAS DAN RESPON PETANI TERHADAP PADI VARIETAS UNGGUL BARU DI KECAMATAN PARUNGKUDA DAN CICANTAYAN KABUPATEN SUKABUMI - Sunjaya Putra; Yati Haryati (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2018)
ABSTRACT Assessment on the productivity and farmers’ responses towards new high yield varieties of rice in Sukabumi Regency, West Java Province. High yielding varieties (HYV) have contributed greatly to the national rice production, but is widely adaptable and not towards a specific area. This study aims to determine the productivity and responsiveness of farmers to new varieties of rice. The assessment was conducted in the rice field of Langensari Village, Parungkuda Subdistrict and Cijalingan Village, Cicantayan Subdistrict, Sukabumi Regency, West Java on Drought II (May-August) 2014, using a Randomized Block Design (RBD) with 6 treatments (varieties) and 4 replications. The varieties used are Inpari 22, Inpari 24, Inpari 25, Inpari 28, Inpari 30 and Ciherang. The parameters observed were: location characteristic was analyzed descriptively, rice yield (GKP) was analyzed by ANOVA (Analysis of variance) followed by Duncan Multiple Range Test at 5% level, farmer response to variety using likert scale, the farmer's response to the organoleptic test was analyzed using freidman test followed by Wilcoxon test and to see the cost, income and profit of farming was done input-output analysis of farming. The results showed that the productivity of new high yielding varieties in Parungkuda Subdistrict was the highest of Inpari 30 varieties (11,20 t/ha GKP) and Cicantayan Inpari 25 (11,15 t/ha GKP). Farmers' responses to rice crops seen from vegetative and generative appearances generally favor all new improved varieties. The response of farmers to the taste of rice in Parungkuda Subdistrict prefered Inpari 22 varieties of rice and the response of farmers to the taste of rice in Cicantayan Subdistrict prefers Inpari 28 and 30. Analysis of farming new varieties (VUB) based on the value of R/C ratio ranges from 4,21 to 6,59 (Inpari 25). productivity, new high yield varieties, farmers' response ABSTRAK Varietas unggul telah memberikan kontribusi besar terhadap produksi padi nasional, namun beradaptasi luas dan belum ke arah spesifik wilayah. Penelitian ini bertujuan untuk mengetahui produktivitas dan respon petani terhadap padi Varietas Unggul Baru. Penelitian dilaksanakan di lahan sawah Desa Langensari Kecamatan Parungkuda dan Desa Cijalingan Kecamatan Cicantayan, Kabupaten Sukabumi Jawa Barat pada Musim Kemarau II (Mei-Agustus) tahun 2014, menggunakan Rancangan Acak Kelompok (RAK) dengan 6 perlakuan (varietas) dan 4 ulangan. Varietas yang digunakan yaitu Inpari 22, Inpari 24, Inpari 25, Inpari 28, Inpari 30 dan Ciherang. Parameter yang diamati meliputi : karakteristik lokasi dianalisis secara deskriptif, produksi padi t/ha (GKP) dianalisis dengan ANOVA (Analysis of varians) dilanjutkan dengan uji DMRT (Duncan Multiple Range Test) pada taraf 5%, respon petani terhadap varietas menggunakan skala likert, respon petani terhadap uji organoleptik dianalisis menggunakan uji friedman dilanjutkan uji Wilcoxon dan untuk melihat biaya, penerimaan serta keuntungan usahatani dilakukan analisis input-output usahatani. Hasil penelitian menunjukkan bahwa produktivitas padi varietas unggul baru di Kecamatan Parungkuda paling tinggi Varietas Inpari 30 (11,20 t/ha GKP) dan di Kecamatan Cicantayan Inpari 25 (11,15 t/ha GKP). Respon petani terhadap tanaman padi dilihat dari penampilan vegetatif dan generatif umumnya menyukai semua varietas unggul baru. Respon petani terhadap cita rasa nasi di Kecamatan Parungkuda lebih menyukai padi varietas Inpari 22 dan respon petani terhadap cita rasa nasi di Kec. Cicantayan lebih menyukai Inpari 28 dan 30. Analisa usahatani varietas unggul baru (VUB) berdasarkan nilai R/C ratio berkisar antara 4,21 hingga 6,59 (inpari 25).produktivitas, varietas unggul baru, respon petani